European Data Protection: Coming of Age - Gutwirth, Serge; Leenes, Ronald; de Hert, Paul; Poullet, Yves (Dordrecht Springer, 2013)
On 25 January 2012, the European Commission presented its long awaited new “Data protection package”. With this proposal for a drastic revision of the data protection framework in Europe, it is fair to say that we are witnessing a rebirth of European data protection, and perhaps, its passage from an impulsive youth to a more mature state. Technology advances rapidly and mobile devices are significantly changing the landscape. Increasingly, we carry powerful, connected, devices, whose location and activities can be monitored by various stakeholders. Very powerful social network sites emerged in the first half of last decade, processing personal data of many millions of users. Updating the regulatory framework was imminent and the presentation of the new package will initiate a period of intense debate in which the proposals will be thoroughly commented upon and criticized, and numerous amendments will undoubtedly be proposed. This volume brings together some 19 chapters offering conceptual analyses, highlighting issues, proposing solutions, and discussing practices regarding privacy and data protection. In the first part of the book, conceptual analyses of concepts such as privacy and anonymity are provided. The second section focuses on the contrasted positions of digital natives and ageing users in the information society. The third section provides four chapters on privacy by design, including discussions on roadmapping and concrete techniques. The fourth section is devoted to surveillance and profiling, with illustrations from the domain of smart metering, self-surveillance and the benefits and risks of profiling. The book concludes with case studies pertaining to communicating privacy in organisations, the fate of a data protection supervisor in one of the EU member states and data protection in social network sites and online media.
Foreword -- I. Concepts -- 1. Seven types of privacy; Rachel Finn, David Wright and Michael Friedewald -- 2. The Internet as Surveilled Workplayplace and Factory; Christian Fuchs and Daniel Trottier -- 3. From Market-Making Tool to Fundamental Right: the Role of the Court of Justice in Data Protection’s Identity Crisis; Orla Lynskey -- 4. Anonymity: a Comparison between the Legal and Computer Science Perspectives; Sergio Mascetti, Anna Monreale, Annarita Ricci and Andrea Gerino -- II. Digital natives and ageing users -- 5. Digital Natives and the Metamorphosis of European Society. The emerging behavioral trends regarding privacy and their legal implications; Norberto Andrade and Shara Monteleone -- 6. Autonomy in ICT for older persons at the crossroads between legal and care practices; Daniel Lopez Gomez, Eugenio Mantovani and Paul De Hert -- 7. Ethical implications of technologies that "support" ageing with dementia at home; Unai Daz-Orueta and Elena Urdaneta -- III. Privacy by design -- 8. Privacy by Design: Enhanced Privacy Leadership, Methods, and Results; Ann Cavoukian -- 9. Roadmap for Privacy Protection in Mobile Sensing Applications; Delphine Christin, Matthias Hollick -- 10. Privacy enhancing techniques for the protection of mobility patterns in LBS: research issues and trends; Maria Luisa Damiani -- 11. Privacy by Design through social requirements analysis of social network sites from a user perspective; Ralf De Wolf, Rob Heyman and Jo Pierson -- IV. Surveillance, profiling and smart metering -- 12. Smart metering and privacy in Europe: lessons from the Dutch case; Colette Cuijpers and Bert-Jaap Koops -- 13. User Choice, Privacy Sensitivity, and Acceptance of Personal Information Collection; Joshua B. Hurwitz -- 14. Beyond Gut Level - Some Critical Remarks on the German Privacy Approach to Smart Metering; Frank Pallas -- 15. Surveillance as a Service? On the Use of Surveillance Data for Administrative Purposes; Martin Pekrek, Arnold Roosendaal and Jasper Sluijs -- 6. Computers Reading Our Minds? The benefits and risks of profiling; Jorg Polakiewicz -- Case studies -- 17. Communicating Privacy in Organisations. Catharsis and Change in the Case of the Deutsche Bahn; Daniel Guagnin, Carla Ilten and Leon Hempel -- 18. The end of independent data protection supervision in Hungary - a case study; Andrs Jri -- 19. Data Protection, Social Networks and Online Mass Media; Artemi Rallo and Ricard Martnez. ..
Online edition
Keywords: Law; Philosophy of law; Technology -- Philosophy; Computer science; Law; Philosophy of law; Technology -- Philosophy; Computer science